Managing founder-based brand identity during succession - Casprini, Elena; Melanthiou, Yioula; Pucci, Tommaso; Zanni, Lorenzo (My University, 2020)
Linking the literature on brand management and family firms, this paper explores how family firms manage a founder-based brand identity during succession. An exploratory case study of an Italian family firm operating in the jewellery sector was conducted. Drawing on the resource-based view of the firm, brand identity is conceived as a resource that needs to be managed across generations. The case analysis highlighted that a joint effort between the first and second generations and non-family members is needed in order to preserve and adapt the family business resources and manage the founder-based brand identity over time.
Keywords: Resource orchestration; Succession; Brand identity; Family firm